SOME PROPERTIES OF MATROIDS OBTAINED FROM CONCEPT LATTICE APPROACHES - mao, hua (Journal of the Indonesian Mathematical Society, 2017)
Using the Hasse diagrams of concept lattices, we investigate the relations between matroids and geometric contexts, followed by judging a mathematical construction to be a matroid. We provide an idea to find out the dual of a matroid from the ways of concept lattice drawing. In addition, we utilize the Hasse diagrams of concept lattices to discuss the minors of matroids, direct sum of matroids and the connectivity of a matroid. All the consequences demonstrate that the theory of concept lattice drawing can be used into matroids. This generalizes the applied fields of concept lattices. DOI : http://dx.doi.org/10.22342/jims.22.2.267.183-190